2011
DOI: 10.5483/bmbrep.2011.44.5.341
|View full text |Cite
|
Sign up to set email alerts
|

The stimulatory effect of CaCl2, NaCl and NH4NO3salts on the ssDNA-binding activity of RecA depends on nucleotide cofactor and buffer pH

Abstract: The single-stranded DNA binding activity of the Escherichia coli RecA protein is crucial for homologous recombination to occur. This and other biochemical activities of ssDNA binding proteins may be affected by various factors. In this study, we analyzed the effect of CaCl2, NaCl and NH4NO3 salts in combination with the pH and nucleotide cofactor effect on the ssDNA-binding activity of RecA. The studies revealed that, in addition to the inhibitory effect, these salts exert also a stimulatory effect on RecA. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Numerous studies have demonstrated that high-concentration salt can modulate the interaction, charge and conformation of DNA in polar solvents [67,68]. For example, not only charge screening but also inhibitory effect on ssDNA binding activity have been observed under high ionic strength condition [67,68].…”
Section: Effect Of Ionic Strengthmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have demonstrated that high-concentration salt can modulate the interaction, charge and conformation of DNA in polar solvents [67,68]. For example, not only charge screening but also inhibitory effect on ssDNA binding activity have been observed under high ionic strength condition [67,68].…”
Section: Effect Of Ionic Strengthmentioning
confidence: 99%
“…For example, not only charge screening but also inhibitory effect on ssDNA binding activity have been observed under high ionic strength condition [67,68]. It is therefore possible to control the nanostructure photoconverted from AgCl in the presence of DNA through choice of salt condition.…”
Section: Effect Of Ionic Strengthmentioning
confidence: 99%
“…There is also a large fraction of genes in the unique genome of RSA3 (12%) encoding for 'repair, replication and recombination' enzymes (for example, methylases and recombinases; Supplementary Table 7), presumably as a consequence of the destabilization effect of salts on biomolecules like DNA and proteins (Ziemienowicz et al, 2011), which also increases homologous recombination events in some microorganisms (Boyandin et al, 2000), preferentially in (halophilic) Archaea than in bacteria (Naor et al, 2012).…”
Section: Core and Variable Gene Inventorymentioning
confidence: 99%